GAMBARAN PRAKTIK MENGGANTI MASKER MASKER BERDASARKAN JENIS MASKER PADA MASYARAKAT DESA SOWAN LOR - Maryam Wulandari; Ari Udijono; Muhammad Arie Wurjanto; Dwi Sutiningsih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
COVID-19 is an infectious disease and was declared a global pandemic on March 11, 2020 by WHO. One way to prevent the spread of the COVID-19 virus is to use a mask. Masks are used for both infected and healthy people. The awareness of the people of Sowan Lor Village in using masks is still relatively low, where the use of masks is only at certain times, and in practice there are still people who replace masks after repeated use. This can lead to inefficient masks in preventing the transmission of the COVID-19 virus. The purpose of this study was to describe the use of masks in the COVID-19 pandemic mass in the people of Sowan Lor Village, Jepara City. This type of research is descriptive using cross sectional method. Samples were taken as many as 102 respondents in the productive age (15-64 years). The results of this study indicate that out of 102 respondents, 53 (52.0%).